The Price Elasticity of Demand for Whole Life Insurance - BABBEL, DAVID F. (Journal of Finance, 1985)
ABSTRACT In this study a real price index is created for whole life insurance sold in the United States from 1953 to 1979. New purchases of whole life insurance are shown to be negatively related to changes in this cost index, contrary to what has been widely accepted in the insurance literature, but consistent with economic theory. The existence of strong price elasticity of demand for whole life insurance does not ensure, however, that the insurance industry manifests a high degree of price competition.